GENDER EQUALITY IN EU-FUNDED PROGRAMS: GLOBAL AND REGIONAL ISSUES - Irina MANOLESCU; Stefana MAFTEI; Carmen Claudia ARUSTEI (EURINT, 2015)
Gender equality is a key issue in EU policies explicitly targeted over 50 years. The reports for the entire period show that progress has been made in the situation for women through specific programs, but the results are always lower than expected. Thus, inequalities persist in several areas, and developments are the source of new challenges. The main objective of this article is to show how gender equality influences EU funded programs and what issues arise depending on the area in which it is applied. We intend to highlight the types of projects that have gender equality objectives and successful models, considering the context in which these projects were carried out and highlighting the determinants of their success. On the way to building a sustainable and inclusive Europe, gender equality encounter many obstacles, particularly in regions where the ideas of existence of disparities and imbalances are not accepted and documented.